Financing Agricultural Research: A Sourcebook - Tabor, Steven R.; Janssen, Willem G.; Bruneau, Hilarion (International Service for National Agricultural Research, 1998)
In spite of a high payoff, agricultural research in many developing countries faces severe financial difficulties. Research leaders need to improve policies, to increase resource mobilization, and to upgrade the management of scarce financial resources. Financing Agricultural Research: A Sourcebook weaves together an assessment of the current research financing situation with a review of available policy options, strategies for improving resource mobilization, and means of enhancing financial management. It is targeted towards leaders of national agricultural research systems, research center directors, heads of research coordinating bodies, as well as those responsible for approving and assigning resources to agricultural research. Research leaders from other sectors may also find answers to the financing issues that they are facing. The book is divided into four sections. They examine key policy options available in today's competitive financing environment, review strategies for improving resource mobilization, look at financial management practices in public research institutes, and review public agricultural research finance in the developing world.